2015
DOI: 10.1186/s13059-015-0839-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide high-throughput deep m6A-seq reveals unique differential m6A methylation patterns between three organs in Arabidopsis thaliana

Abstract: Backgroundm6A is a ubiquitous RNA modification in eukaryotes. Transcriptome-wide m6A patterns in Arabidopsis have been assayed recently. However, differential m6A patterns between organs have not been well characterized.ResultsOver two-third of the transcripts in Arabidopsis are modified by m6A. In contrast to a recent observation of m6A enrichment in 5′ mRNA, we find that m6A is distributed predominantly near stop codons. Interestingly, 85 % of the modified transcripts show high m6A methylation extent compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
233
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(264 citation statements)
references
References 135 publications
31
233
0
Order By: Relevance
“…m 6 A deposition is also positively correlated with the abundance of a large fraction of A. thaliana transcripts, suggesting that it has regulatory roles in plant gene expression 51 . Another study found that m 6 A patterns differ between plant organs, suggesting that m 6 A affects organogenesis and has cell-type specific functions 145 . Numerous homologues of mammalian m 6 A demethylases and the YT521-B homology (YTH) domain reader proteins exist in plant genomes.…”
Section: Figurementioning
confidence: 99%
“…m 6 A deposition is also positively correlated with the abundance of a large fraction of A. thaliana transcripts, suggesting that it has regulatory roles in plant gene expression 51 . Another study found that m 6 A patterns differ between plant organs, suggesting that m 6 A affects organogenesis and has cell-type specific functions 145 . Numerous homologues of mammalian m 6 A demethylases and the YT521-B homology (YTH) domain reader proteins exist in plant genomes.…”
Section: Figurementioning
confidence: 99%
“…m 6 A is found within a conserved consensus sequence (G/A)(G/A) A CU (with a preference for (G/A)G A CU) in different eukaryotes (Horowitz et al ., 1984; Narayan & Rottman, 1988; Dominissini et al ., 2012; Meyer et al ., 2012; Luo et al ., 2014; Wan et al ., 2015). However, only a subset of potential sites is actually modified and the mechanisms underlying the specificity of writing are not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…N 6 -methyladenosine (m 6 A) is one of the most prevalent modifications of eukaryotic mRNAs [4] with conserved topology across yeast [5], Arabidopsis thaliana [6, 7], Drosophila [8], mouse and human [9, 10]. Most of the m 6 A sites share a similar consensus m 6 A motif, RRm 6 ACH, where R represents a purine and H represents a non-guanine base [9].…”
Section: Introductionmentioning
confidence: 99%
“…Genes with m 6 A methylation mainly enriched in biologically important pathways, such as regulation of gene expression, differentiation and metabolism [6, 7, 9]. Nonetheless, m 6 A methylation profiles and functions in tissue at postnatal developmental stages have rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%